Impact of time from diagnosis to initiation of curative chemotherapy on survival of patients with diffuse large B-cell lymphoma. Issue 2 (1st February 2016) - Hay, Kevin; Lee, Benny; Goktepe, Ozge; Connors, Joseph M.; Sehn, Laurie H.; Savage, Kerry J.; Klasa, Richard; Shenkier, Tamara; Gerrie, Alina; Villa, Diego
Abstract : Although it is generally regarded appropriate to start chemotherapy promptly after a diagnosis of diffuse large B-cell lymphoma (DLBCL), the optimal time from diagnosis to treatment (TDT) is unknown. A total of 689 patients diagnosed with DLBCL and treated with ≥ 1 cycle of CHOP-R with curative intent during 2003–2008 in British Columbia were identified: 347 (50%) TDT ≤ 4 weeks, 277 (40%) TDT 5–8 weeks, 65 (10%) TDT > 8 weeks. For the respective TDT groups, 5-year OS estimates were 61%, 74%, 63% ( p = 0.006); 5-year PFS 57%, 70%, 61% ( p = 0.006); and 5-year DSS 64%, 80%, 77% ( p <0.001). In multivariate analysis, TDT >8 weeks was associated with worse OS (HR 1.20 (95% CI 1.03, 1.41), p = 0.020), PFS (HR 1.33 (95% CI 1.15, 1.54), p < 0.001), and DSS (HR 1.40 (95% CI 1.10, 1.78), p = 0.006). Clinicians should endeavor to initiate curative chemotherapy as soon as possible after a diagnosis of DLBCL is established.